Site-specific primary nutrients recommendation in wheat (Triticum aestivum L.) for sustainable productivity and increasing profitability - MAURIYA, A. K.; MAURYA, V. K.; MISHRA, P. K.; VERMA, R. B. (Journal of Soil and Water Conservation, 2021)
A field experiment was conducted for two years (2006-07 and 2007-08) at CRS Masodha, Faizabad during rabi season on silty loam soil to assess the contribution of various nutrients towards sustainable productivity and increasing profitability of wheat, in rice-wheat system in eastern plain zone of Uttar Pradesh by using nutrient omission/deletion plot technique. The results revealed with the application of 150:60:120 kg NPK ha-1 to wheat crop production after harvesting of rice crop recorded higher yield attributes, grain yield, straw yield, nutrient uptake (NPK) and available nutrients in soil (NPK) as compared to farmer’s practice and recommended practice as well as deletion of phosphorus and potassium from 150:60:120 kg NPK ha-1. Balance dose of nutrients (N150P60K120 kg ha-1) produced 61.7 to 88.9% and 21.7 to 29.4% higher grain yield over farmer’s practice and recommended practice, respectively. Highest net return of Rs. 40,100 and 38,700 ha-1 with highest B:C ratio of 2.11 and 2.01 obtained with balance dose of nutrients in 2006-07 and 2007-08, respectively, which was 21,300 and 24,800 higher over those of farmer’s practice as well as 12,500 and 9,400 more than the recommended practice during 2006-07 and 2007-08, respectively. However, soil fertility status increased with increasing level of NPK upto N150 P60 K120 kg ha-1. Thus, the results suggested that the application of 150:60:120 kg of NPK ha-1 to wheat after harvesting of rice is required for achieving sustainable productivity and increasing profitability of wheat.